2020
DOI: 10.1093/cid/ciaa1703
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blinded, Placebo-Controlled Phase 2 Trial of an Inactivated Severe Acute Respiratory Syndrome Coronavirus 2 Vaccine in Healthy Adults

Abstract: Background We evaluated an inactivated SARS-CoV-2 vaccine for immunogenicity and safety in adults aged 18-59 years. Methods In this randomized, double-blinded and controlled trial, healthy adults received a medium (MD) or a high dose (HD) of the vaccine at an interval of either 14 days or 28 days. Neutralizing antibody (NAb) and anti-S and anti-N antibodies were detected at different times, and adverse reactions were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 7 publications
3
91
1
Order By: Relevance
“…This work adds to the literature by demonstrating that the FNR of SARS-CoV-2 molecular assays is low [ 1 , 27 , 28 ] and subject to viral load dynamics over time. However, the interpretation of COVID-19 test results should be conducted in the overall context of each patient’s clinical presentation [ 9 , 29 ], with repeat testing advised should post-test probability upon follow-up clinical evaluation remain high.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…This work adds to the literature by demonstrating that the FNR of SARS-CoV-2 molecular assays is low [ 1 , 27 , 28 ] and subject to viral load dynamics over time. However, the interpretation of COVID-19 test results should be conducted in the overall context of each patient’s clinical presentation [ 9 , 29 ], with repeat testing advised should post-test probability upon follow-up clinical evaluation remain high.…”
Section: Resultsmentioning
confidence: 80%
“…Data from earlier in the pandemic reported FNRs of up to 30% [ 6 ] with a systematic review on the topic reporting ranges from 2 to 29% [ 2 ]. A large study from New York evaluating the clinical performance of SARS-CoV-2 molecular testing found that on average up to 17% of positives were missed by the first test [ 22 ], while another American study reported a FNR of 3.5% in patients with discordant swab results within a 7-day period [ 1 ]. Two other studies have estimated sensitivities ranging from 89 to 94.6% [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from measles virus and vesicular stomatitis virus (VSV) based vaccine candidates in animal models were also reported (Horner et al, 2020;. Three studies reported preliminary results on the safety and immunogenicity of inactivated COVID-19 vaccines from phase I/II clinical trials (Che et al, 2020;Zhang et al, 2020g). The inactivated vaccines demonstrated acceptable safety profiles and were effective in inducing neutralizing antibodies.…”
Section: Progress Of Covid-19 Vaccine Developmentmentioning
confidence: 99%
“…Through the protocol, we have not seen any COVID-19 cases attributed to AFTs, although we cannot rule out possibilities of asymptomatic cases without repeated PCR tests. The PCR testing at our institution has specificity of 99.9% and false-negative rate of 2.8% [ 3 , 4 ]. When combined with testing at other facilities, they may differ, and infection risk during AFTs may change due to patients from other counties or states.…”
mentioning
confidence: 99%